Evaluation of Bioequivalence Between the New Procaterol Hydrochloride Hydrate Dry Powder Inhaler and the Approved Dry Powder Inhaler in Patients With Asthma in a Randomized, Double‐Blind, Double‐Dummy, Crossover Comparison Study: A Phase 3 Study. Issue 4 (8th September 2017) - Shirai, Ryo; Suzaki, Yuki; Sato, Kyoko; Takeuchi, Yuko; Tokimatsu, Issei; Koga, Nobuyuki; Kadota, Junichi; Ohashi, Kyoichi
Abstract: Procaterol hydrochloride hydrate (procaterol) is a β2 ‐adrenergic receptor agonist that induces a strong bronchodilatory effect. The procaterol dry powder inhaler (DPI) has been frequently used in patients with bronchial asthma or chronic obstructive pulmonary disease. We evaluated the bioequivalence and safety between the new procaterol DPI (new DPI) and the approved procaterol DPI (approved DPI). This study was a randomized, double‐blind, double‐dummy, crossover comparison to evaluate the pharmacodynamic equivalence of the new DPI and the approved DPI in patients with bronchial asthma. Primary efficacy variables were area under the concentration‐time curve (AUC) forced expiratory volume in the first second (FEV1 )/h and maximum FEV1 during the 480‐minute measurement period. Patients were divided into 2 groups, New‐DPI‐First (n = 8) and Approved‐DPI‐First (n = 8), according to the investigational medical product that was administered first. Patients inhaled 20 μg of procaterol in each period. FEV1 was measured by a spirometer at predose and at 15, 30, 60, 90, 120, 180, 240, 360, and 480 minutes after each investigational medical product administration. Equivalence was evaluated by confirming that the 2‐sided 90%CIs for the difference between the new and the approved DPI in means of AUC (FEV1 )/h and maximum FEV1 were within the acceptance criteria of –0.15 to 0.15 L. The difference in means of AUC (FEV1 )/h and maximum FEV1 was 0.041 L and 0.033 L, respectively, and the 90%CI was 0.004 to 0.078 L and –0.008 to 0.074 L, respectively. These CIs were both within the acceptance criteria. The new DPI was assessed as being bioequivalent to the approved DPI.